A Case Study of the Use of Wikipedia among English Department Students of Andalas University - Hanafi, Hanafi; Rianita, Dian (Universitas PGRI Adi Buana Surabaya, 2021)
This article reports an investigation of university students’ use of online Wikipedia site in writing their assignment or research report. Data were collected through a survey questionnaire and interview. First of all, a survey questionnaire was distributed among the learners (n=70) identifying their computer and internet literacy, frequency, strategy, and future orientation of using Wikipedia for their writing assignments or essays. Then, interviews with some lecturers (N=8) revealed teachers’ lack of awareness and agreement of Wikipedia in academic writing, partially due to the absence of Departmental policy. As the results, despite being already informed of the encyclopedia’s academic unreliability, Indonesian EFL informants in this study were proven to be familiar with computer and capable of using internet and incorporating Wikipedia materials when writing their essays at Andalas University. The data also indicated that students had improved their techniques of using the Wikipedia from copying-and-pasting to editing and paraphrasing. Half of them did not cross check Wikipedia article’s citations and references. Therefore, students’ awareness of the ease of Wikipedia may have encouraged them to consciously plagiarize in addition to the absence of their lecturers’ awareness upon this issue.